Predisposing Factors and Aetiologic Diagnosis of Infectious Corneal Ulcer - Ahmed, Sharmeem; Ghosh, Anamica; Hassan, Syed A; Tarafder, Shirin; Amin Miah, Md Ruhul (Bangladesh Journal of Medical Microbiology, 2011)
This cross-sectional study was carried out to identify causative pathogens and to determine the demographic characteristics and predisposing factors of corneal ulcer presenting at tertiary care hospitals in Dhaka. A total of 250 samples (corneal swab and scrapings) were collected from clinically diagnosed corneal ulcer patients attending Bangabandhu Sheikh Mujib Medical University and Islamia Eye Hospital from February, 2004 to January, 2005. Out of 250 samples, microbial infection was established in 147 (58.8%) cases by culture and microscopy in which 82 (32.8%) patients showed fungal growth, 52 (20.8%) cases had bacterial growth and 13 (5.2%) cases had mixed bacterial & fungal growth. Aspergillus species 48 (50.53%) were the most common fungal isolates followed by Fusarium species 25 (26.32%). The predominant bacterial isolates were Staphylococcus epidermidis 22(32.85%) followed by Staphylococcus aureus 17 (26.15%) and Pseudomonas species 13 (20%). Out of 147 cases a larger group of patients (105, 71.43%) were in middle age group (21 to 50 years). Males (95, 64.63%) were more often affected (P<0.001). A majority of patients (114, 77.55%) came from rural areas (P<0.001), and most patients (55, 37.41%) of bacterial & fungal keratitis were farmers. Ocular trauma (87, 59.18%) was a highly significant risk factor (P<0.001) of which mostly (41, 27.89%) were due to agricultural materials. The findings of this study would help the ophthalmologists in the management of their patients with keratitis. Keywords: Corneal Ulcer, Infective Keratitis, Predisposing factors. DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8466 BJMM 2011; 4(1): 28-31